Musicophilia : tales of music and the brain - Sacks, Oliver W (New York : Alfred A. Knopf, 2007)
Music can move us to the heights or depths of emotion. It can persuade us to buy something, or remind us of our first date. It can lift us out of depression when nothing else can. It can get us dancing to its beat. But the power of music goes much, much further. Indeed, music occupies more areas of our brain than language does--humans are a musical species. Oliver Sacks's compassionate, compelling tales of people struggling to adapt to different neurological conditions have fundamentally changed the way we think of our own brains, and of the human experience. Here, he examines the powers of music through the individual experiences of patients, musicians, and everyday people. Music is irresistible, haunting, and unforgettable, and Oliver Sacks tells us why.--From publisher description
Preface Part I: Haunted by Music A Bolt from the Blue: Sudden Musicophilia A Strangely Familiar Feeling: Musical Seizures Fear of Music: Musicogenic Epilepsy Music on the Brain: Imagery and Imagination Brainworms, Sticky Music, and Catchy Tunes Musical Hallucinations Part II: A Range of Musicality Sense and Sensibility: A Range of Musicality Things Fall Apart: Amusia and Dysharmonia Papa Blows His Nose in G: Absolute Pitch Pitch Imperfect: Cochlear Amusia In Living Stereo: Why We Have Two Ears Two Thousand Operas: Musical Savants An Auditory World: Music and Blindness The Key of Clear Green: Synesthesia and Music Part III: Memory, Movement, and Music In the Moment: Music and Amnesia Speech and Song: Aphasia and Music Therapy Accidental Davening: Dyskinesia and Cantillation Come Together: Music and Tourette's Syndrome Keeping Time: Rhythm and Movement Kinetic Melody: Parkinson's Disease and Music Therapy Phantom Fingers: The Case of the One-Armed Pianist Athletes of the Small Muscles: Musician's Dystonia Part IV: Emotion, Identity, and Music Awake and Asleep: Musical Dreams Seduction and Indifference Lamentations: Music and Depression The Case of Harry S.: Music and Emotion Irrepressible: Music and the Temporal Lobes A Hypermusical Species: Williams Syndrome Music and Identity: Dementia and Music Therapy Acknowledgments Bibliography Index
Includes bibliographical references (pages 353-367) and index
Keywords: Music -- Physiological aspects